2016
DOI: 10.1007/s10646-016-1618-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the exposure to atrazine on bone development of Podocnemis expansa (Testudines, Podocnemididae)

Abstract: The use of pesticides is a widely spread practice in Brazilian agriculture, and dispersion of these substances is an important factor for the fauna and flora. Atrazine is an endocrine disruptor in the xenoestrogen class that is used worldwide in agricultural practices. In Brazil, its use is permitted in several crops. Podocnemis expansa is a representative of the Testudines order that is the largest freshwater reptile of South America. Its distribution enables it to get in contact with molecules that are commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Pesticides may cause a transient or permanent alteration of the immune system, leading to higher risks for chronic health disorders, including hematological and immune alterations such as inflammation and cytokine modulation [ 98 , 110 , 111 , 112 , 113 ]. Recently, the intestinal microbiota has emerged as a notable factor regulating pesticides’ toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides may cause a transient or permanent alteration of the immune system, leading to higher risks for chronic health disorders, including hematological and immune alterations such as inflammation and cytokine modulation [ 98 , 110 , 111 , 112 , 113 ]. Recently, the intestinal microbiota has emerged as a notable factor regulating pesticides’ toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study with developmental ATZ exposure in chick embryos also showed neural tube defects and craniofacial hypoplasia ( Joshi et al 2013 ). Conversely, a developmental exposure in South American river turtles found no visual changes with ATZ exposure in whole body skeletal structures ( dos Santos Mendonça et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the analysis, two papers overlooked during the development of the original WoE assessment were identified and analyzed. In the end, the papers included in the QWoE update are: (Chang et al 2005;Hecker et al 2005;Svartz et al 2012;Ghodageri and Katti 2013;Olker 2014;Shenoy 2014;Baxter et al 2015;Chen et al 2015;Sai et al 2015Sai et al , 2018Syngenta 2015Syngenta , 2017aSyngenta , 2017bVan Der Kraak et al 2015;Wirbisky and Freeman 2015;dos Santos Mendonc¸a et al 2016;Ehrsam et al 2016;Gustafson et al 2016;Khan et al 2016aKhan et al , 2016bKhan et al , 2016cLiu et al 2016;Richter et al 2016;Russart and Rhen 2016;Tulaby Dezfuly and Mohammadian 2016;Wirbisky et al 2016aWirbisky et al , 2016bWirbisky et al , 2016cD'Angelo and Freeman 2017;Du Gas et al 2017;Hoskins et al 2017;Jones et al 2017;Khalil et al 2017;Kirsten et al 2017;McMahon et al 2017;Persch et al 2017;Scott et al 2017;Shukla et al 2017;Snyder et al 2017;Wang et al 2017;…”
Section: Methodsmentioning
confidence: 99%